2016
DOI: 10.1186/s12910-016-0154-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of healthcare ethics among resident doctors and ward nurses from a resource poor setting, Nepal

Abstract: BackgroundHealthcare ethics is neglected in clinical practice in LMICs (Low and Middle Income Countries) such as Nepal. The main objective of this study was to assess the current status of knowledge, attitude and practice of healthcare ethics among resident doctors and ward nurses in a tertiary teaching hospital in Nepal.MethodsThis was a cross sectional study conducted among resident doctors (n = 118) and ward nurses (n = 86) in the largest tertiary care teaching hospital of Nepal during January- February 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
69
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 28 publications
12
69
1
1
Order By: Relevance
“…Also, most of the study participants (92.9% of paramedical and 86.1% of administrative teams) agreed that the Ethics Committee of Scientific Research is useful. This was in agreement with Adhikari et al study where 98.8% nurses (85 out of 86) agreed that ethics course should be taught in every medical/nursing teaching institution [11].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, most of the study participants (92.9% of paramedical and 86.1% of administrative teams) agreed that the Ethics Committee of Scientific Research is useful. This was in agreement with Adhikari et al study where 98.8% nurses (85 out of 86) agreed that ethics course should be taught in every medical/nursing teaching institution [11].…”
Section: Discussionsupporting
confidence: 90%
“…Regarding research ethics knowledge of the study participants, more than 90% of the paramedical team and two thirds of the administrative team knew about research ethics and knew that doing a research on patient or use their data without their permission is not ethical or permissible. This result was in agreement with Adhikari et al's study where 96.5% of nurses knew the importance of confidentiality and patient data security [11] and also in Aliyu et al's study where the majority of the nurse participants (82.6%, 114 out of 138 ) possess good knowledge of ethical dilemma [12].…”
Section: Discussionsupporting
confidence: 90%
“…Several items and sections of this questionnaire were used by other studies. (20,24,27) This questionnaire was pilot-tested on 15 medical residents to identify ambiguous or difficult questions, acceptability of questions and the time needed to complete the questionnaire. Respondents were asked to give their feedback and their comments on an external sheet, and minor changes were made accordingly.…”
Section: Questionnaire Developmentmentioning
confidence: 99%
“…(15)(16)(17)(18)(19) Several studies revealed that medical residents face many ethical challenges, sometimes on a daily basis, in addition to their negative attitudes and low level of knowledge. (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) Therefore, the present study aimed to assess the baseline knowledge, attitudes and practices (KAPs) of medical residents in the Islamic Hospital in Amman (2017) towards healthcare ethics.…”
Section: Introductionmentioning
confidence: 99%
“…[9,11,15] This can be done by incorporating research ethics in university curricula and training of researchers. [16]. b) The national guidelines need to be revised to help researchers to deal with vulnerable populations including people with mental disorders.…”
Section: Responsibility Of Research Participantsmentioning
confidence: 99%